2022
DOI: 10.1029/2021jd036222
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Gravity Waves to Universal Vertical Wavenumber (∼m−3) Spectra Revealed by a Gravity‐Wave‐Permitting General Circulation Model

Abstract: Observations with high vertical resolution have revealed that power spectra of horizontal wind and temperature fluctuations versus vertical wavenumber m $m$ have a universal shape with a steep slope in a high m $m$ range, approximately proportional to m−3 ${m}^{-3}$. Several theoretical models explaining this spectral slope were proposed under an assumption of gravity wave (GW) saturation. However, little evidence has been obtained to show that these universal spectra are fully composed of GWs. To confirm the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…The dependency of GW morphology on the model's horizontal resolution is briefly discussed in this study. Okui et al (2022) examined vertical wavenumber (m) spectra in the same GCM and showed that characteristics of the model-simulated m spectra of GWs were broadly consistent with observations. These earlier studies support the reality of GWs in our GCM simulations.…”
mentioning
confidence: 66%
“…The dependency of GW morphology on the model's horizontal resolution is briefly discussed in this study. Okui et al (2022) examined vertical wavenumber (m) spectra in the same GCM and showed that characteristics of the model-simulated m spectra of GWs were broadly consistent with observations. These earlier studies support the reality of GWs in our GCM simulations.…”
mentioning
confidence: 66%
“…The details of the model are described by Watanabe and Miyahara (2009) and Okui et al. (2021, 2022). Here we shortly present the configuration of the model and simulations.…”
Section: Datamentioning
confidence: 99%
“…The DJF of 2018/2019 includes an SSW event that occurred in January 2019. The details of the model are described by Journal of Geophysical Research: Atmospheres 10.1029/2023JD039881 Watanabe and Miyahara (2009) and Okui et al (2021Okui et al ( , 2022. Here we shortly present the configuration of the model and simulations.…”
Section: High-resolution Jaguar Hindcastsmentioning
confidence: 99%
“…In this sense, intercomparison of satellite observations is worthwhile. .g., VanZandt, 1985;Tsuda et al, 1989;Sato et al, 2003) , which is characterized by a steep slope of vertical wavenumber (𝑚) spectra (∝ ~𝑚 ) at high wavenumbers of 𝑚= ~10 -4 -10 -3 m -1 (Okui et al, 2022). Kruse et al (2022) (Becker et al, 2022;Kruse et al, 2022).…”
Section: Hosted Filementioning
confidence: 99%